Persepsi siswa SMPN 3 Srengat Blitar dalam implementasi pembelajaran hybrid pada mata pelajaran IPS - Umar, Harits Abdullah; Wiradimadja, Agung (Universitas Negeri Malang, 2023)
The COVID-19 pandemic has gradually declined after more than 2 years of attacking Indonesia. This has led the government to relax the regional quarantine policy (PPKM) slightly. After the issuance of MENDIKBUD RISTEK Circular Letter No. 4 of 2021 concerning the implementation of face-to-face learning during the COVID-19 pandemic, learning that was originally carried out completely online is now allowed to carry out limited face-to-face learning. The purpose of this research is to find out the opinions of students, as well as to find out the process of implementing hybrid learning in social studies subjects at SMPN 3 Srengat which took place during the COVID-19 pandemic. This research uses a descriptive type quantitative approach. The results showed that hybrid learning was considered effective as evidenced by the dominant percentage of SMPN 3 Srengat students, in the implementation of hybrid learning in social studies subjects, students' understanding was still lacking because social studies is one of the contextual subjects and really needs the role of the teacher in explaining in class (face-to-face, not with online learning). Pandemi COVID-19 berangsur menurun setelah lebih dari 2 tahun menyerang Indonesia. Hal ini membuat pemerintah sedikit melonggarkan kebijakan karantina wilayah (PPKM). Setelah diterbitkannya Surat Edaran MENDIKBUD RISTEK No. 4 Tahun 2021 tentang pelaksanaan pembelajaran tatap muka di masa pandemi COVID-19, pembelajaran yang semula dilaksanakan sepenuhnya daring kini dapat dilakukan secara terbatas dengan tatap muka. sedang belajar. Tujuan penelitian ini adalah untuk mengetahui pendapat siswa, serta untuk mengetahui proses penerapan hybrid learning pada mata pelajaran IPS di SMPN 3 Srengat yang berlangsung pada masa pandemi COVID-19. Penelitian ini menggunakan pendekatan kuantitatif tipe deskriptif. Hasil penelitian menunjukkan bahwa pembelajaran hybrid dianggap efektif dibuktikan dengan persentase siswa SMPN 3 Srengat yang dominan, dalam penerapan pembelajaran hybrid pada mata pelajaran IPS, pemahaman siswa masih kurang karena IPS merupakan salah satu mata pelajaran kontekstual dan sangat dibutuhkan. peran guru dalam menjelaskan di kelas (tatap muka, bukan dengan pembelajaran daring).